Pozostałości prawa religijnego we współczesnym prawie - Najman, Michał (PRAWO i WIĘŹ, 2025)
Religion and law mutually interpenetrated and influenced each other both in the early stages of the formation of society and in the further processes of its development. It is impossible to say clearly which of them developed earlier, or which had a greater influence on the contemporary form of the other. At present, the relationship between law and religion is rarely discussed. The dominant view proclaiming the secularization of law, while undoubtedly justified, seems to overlook the religious origins of many contemporary purportedly secular lega institutions, such as the principle of equality before the law, social policy, parental authority or posthumous protection of personal rights. It seems that departing from the religious justification of legal institutions is the right solution, which push legal sciences to seek explanations of the functioning of legal institutions. The aim of this paper is to show that law and religion mutually interpenetrated during the period of creation of their final forms, which resulted in the popularization of legal institutions derived from religious norms. This facilitates the creation (or denotation) of legally protected values ​​and the search for their scientific (non-religious) foundations.